Indirect Effects From Childhood Sexual Abuse Severity to PTSD: The Role of Avoidance Coping - Batchelder, Abigail W. (Journal of interpersonal violence, 2021)
Men who have sex with men (MSM) disproportionately experience childhood sexual abuse (CSA) compared with heterosexual men, often resulting in continued trauma-related sequelae, including symptoms of posttraumatic stress disorder (PTSD) such as avoidance. The variability in trauma-related sequelae may be associated with chronicity or duration of CSA. The relationship between duration of CSA and later PTSD symptom severity is not well understood, including the extent coping strategies account for these relationships. We used linear regression to examine these relationships and to assess the indirect effects of avoidance (behavioral disengagement and denial) and adaptive coping strategies on the relationship between CSA duration and adult PTSD symptom severity on a diverse sample included 290 MSM with a history of CSA. In adjusted models, CSA duration was significantly associated with adult PTSD symptom severity (standardized β = .23, p < .000) and with avoidance coping (standardized β = .19, p = .002). Separating this out, behavioral disengagement was significantly associated with CSA duration (standardized β = .20, p = .001) but denial was not. In adjusted analyses assessing indirect effects, avoidance coping partially accounted for the relationship between CSA duration and total trauma symptom severity (standardized β reduced from .23 to .17; Sobel = 2.90, p = .004). Similarly, behavioral disengagement partially accounted for the association between CSA duration and total symptoms (standardized β reduced from .23 to .18; Sobel = 2.68, p = .007). Avoidance coping, and behavioral disengagement specifically, may play a role in the severity of PTSD symptoms experienced by MSM with CSA histories. This work emphasizes the need for clinicians to consider behavioral disengagement in understanding PTSD symptom severity among MSM with histories of CSA.